Survey of heavy metals concentration (Pb,Cd,As,Hg) in vegetables of riverbank farmlands of Mashhad Kashafrood river-2018 - ghasem ranjbar; Ali Asghar Najafpoor; Aliakbar Dehghan (Mashhad University of Medical Sciences, 2020)
Background and Objective: The main and most important way for heavy metals to enter human body is eating food. Given that vegetables are among main food sources. For this purpose, in this study heavy metals concentrations (lead, cadmium, Arsenic and mercury) in water and wastewater used, soil and vegetables of Kashafrood margin River farms are investigated. Materials and Methods: In this in vitro study, 54 samples of three vegetable types and 18 water and wastewater samples and 18 soil samples were taken from three farms (one control and two case farms) in two consecutive months. The case farms were selected in Kashafrood River vicinity, where flow treatment plants municipal sewage and wastewater in Mashhad city. After preparation, samples acid digestion action was performed according to standard methods (3030 F Standard Method for water and vegetables - 3050 B EPA for soil). Atomic absorption device (spectrometry) was used to determine the concentration of heavy metals in samples and SPSS and Excel software were used to analyze the data. Finally, the information obtained was compared with national and international standards. Results: The mean concentrations of heavy metals (lead, cadmium, arsenic and mercury) in water, soil and vegetable samples were different and varied in time and place. Among the selected vegetables, dill samples, among farms, farm 2 and among months June illustrated most polluted one, and of the heavy metals in the samples, lead had highest concentrations. Conclusion: Heavy metal concentrations in soil and water samples were within national and international standard range, while concentrations of these metals in some vegetable samples exceeded national and international levels, which may be due to other factors, however, the use of standard effluent for agricultural irrigation requires control measures and the performance of relevant machinery duties. Keywords: Vegetables, Kashafrood, Heavy Metals